The Modified Arch Landing Areas Nomenclature (MALAN) Improves Prediction of Stent Graft Displacement Forces: Proof of Concept by Computational Fluid Dynamics Modelling. (April 2018) - Marrocco-Trischitta, Massimiliano M.; van Bakel, Theodorus M.; Romarowski, Rodrigo M.; de Beaufort, Hector W.; Conti, Michele; van Herwaarden, Joost A.; Moll, Frans L.; Auricchio, Ferdinando; Trimarchi, Santi
Abstract : Objective: To assess whether the Modified Arch Landing Areas Nomenclature (MALAN), which merges Ishimaru's map with the Aortic Arch Classification, predicts the magnitude of displacement forces and their orientation in proximal landing zones for TEVAR. Methods: Computational fluid dynamic (CFD) modelling was employed to prove the hypothesis. Healthy aorta CT angiography scans were selected based on aortic arch geometry to reflect Types I to III arches equally (each n  = 5). CFDs were used to compute pulsatile displacement forces along the Ishimaru's landing zones in each aorta including their three dimensional orientation along the upward component and sideways component. Values were normalised to the corresponding aortic wall area to calculate equivalent surface traction (EST). Results: In Types I and II arches, EST did not change across proximal landing zones ( p  = .297 and p  = .054, respectively), whereas in Type III, EST increased towards more distal landing zones ( p  = .019). Comparison of EST between adjacent zones, however, showed that EST was greater in 3/II than in 2/II ( p  = .016), and in 3/III than in 2/III ( p  = .016). Notably, these differences were related to the upward component, that was four times greater in 3/II compared with 2/II ( p  < .001), and five times greater in 3/III compared with 2/III ( p  < .001). Conclusion: CFD modelling suggests that MALAN improves discrimination of expected displacement forces in proximal landing zones for TEVAR, which might influence clinical outcomes. The clinical relevance of the finding, however, remains to be validated in a dedicated post-operative outcome analysis of patients treated by TEVAR of the arch.